2004
DOI: 10.1086/426034
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Sex-Specific Risk Alleles in Autism Spectrum Disorder

Abstract: We investigated the genetic aspects of the large sex bias in the prevalence of autism spectrum disorder by monitoring changes in linkage when the family set for an affected sibling pair genome scan is subdivided on the basis of the sex of affected children. This produces a significant excess in the total number of linkage peaks (P=1.3 x 10(-8)) and identifies a major male-specific linkage peak at chromosome 17q11 (P<.01). These results suggest that sexual dichotomy is an important factor in the genetics of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 19 publications
8
135
0
3
Order By: Relevance
“…The primary analysis was an affected sib-pair genome scan to detect autism loci using the diagnosis as the phenotype. Our secondary analyses attempted to replicate specific regional linkage signals reported by others who stratified their sample using gender, 20 developmental regression, 27 and language acquisition. 29 Our tertiary analyses explored the possibility of additional regions with relevant loci by completing the scan for the rest of the genome using strata defined by the same gender, developmental regression and language acquisition phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary analysis was an affected sib-pair genome scan to detect autism loci using the diagnosis as the phenotype. Our secondary analyses attempted to replicate specific regional linkage signals reported by others who stratified their sample using gender, 20 developmental regression, 27 and language acquisition. 29 Our tertiary analyses explored the possibility of additional regions with relevant loci by completing the scan for the rest of the genome using strata defined by the same gender, developmental regression and language acquisition phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Notably missing from our genome scan were signals corresponding to those reported by others on chromosome 2 13,16,17,23,45 and chromosome 17. 14,20,24 Gender and linkage analyses Previous work by others suggested that linkage signals on chromosomes 4, 14,20 7, 17 and 17 14,20 were dependent on the gender of the affected individuals in the families. To attempt to replicate these findings, we used the same stratification design, dividing our sample into families with only male affected individuals (MO families; 113 strict, 148 broad), and families with at least one affected female sib (FC families; 56 strict, 74 broad; Table S4).…”
Section: Primary Genome Scanmentioning
confidence: 99%
See 3 more Smart Citations